2019
DOI: 10.3389/fimmu.2019.01906
|View full text |Cite
|
Sign up to set email alerts
|

CD8+ T Lymphocyte and NK Cell Network: Circuitry in the Cytotoxic Domain of Immunity

Abstract: Multiple effector layers in the immune system ensure an optimal temporal and spatial distribution of immune defense. Cytotoxic innate lymphoid natural killers (NK) and adaptive CD8 + T lymphocytes (CTL) interact to elicit specific cytolytic outcomes. The CTL carry antigen-specific T cell receptors (TCR) to recognize cognate peptides bound with major histocompatibility complex class-I (MHC-I) or human leukocyte antigen (HLA) molecules on target cells. Upon TCR engagement with MHC-I:peptid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(63 citation statements)
references
References 79 publications
1
61
0
1
Order By: Relevance
“…While these cell types share transcriptional signatures, our results suggest both independently contribute to disease. The predominant cytotoxic cells of the immune system, CD8 + T-cells and NK cells are equipped to kill infected or otherwise compromised cells and operate in synchrony, interacting directly and indirectly to co-regulate one another( Uzhachenko and Shanker, 2019 ). NK cell depletion is known to prevent CD8 + T-cell exhaustion( Cook and Whitmire, 2013 ; Waggoner et al, 2011 ), and the absence of NK-dependent clonal expansion of CD8 + T-cell exhaustion after viral infection can lead to severe and even fatal T-cell immunopathology( Cook and Whitmire, 2013 ; Waggoner et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…While these cell types share transcriptional signatures, our results suggest both independently contribute to disease. The predominant cytotoxic cells of the immune system, CD8 + T-cells and NK cells are equipped to kill infected or otherwise compromised cells and operate in synchrony, interacting directly and indirectly to co-regulate one another( Uzhachenko and Shanker, 2019 ). NK cell depletion is known to prevent CD8 + T-cell exhaustion( Cook and Whitmire, 2013 ; Waggoner et al, 2011 ), and the absence of NK-dependent clonal expansion of CD8 + T-cell exhaustion after viral infection can lead to severe and even fatal T-cell immunopathology( Cook and Whitmire, 2013 ; Waggoner et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Upon activation, CD8+ T cells differentiate into cytotoxic T cells (CTLs), which is the major functional subpopulation. CTL can specifically recognize endogenous antigenic peptides presented by the major histocompatibility complex I, thereby killing tumor cells 26 . We conducted the GSVA analyses to compare the differences of pathways between the GGN-ADC-derived and SADC-derived CD8+ T cells (Fig.…”
Section: The Immunosuppressive Pathways Were Activated In T Cells Dermentioning
confidence: 99%
“…To analyze the immune landscape of OV, consistent clustering was used to divide OV samples on the basis of the proportion of the 23 TME cell types. As a result, four new cell subtypes of OV were identified and named according to the functions of the cells: the immune procancer cell subtype (IPCCS, n = 52) ( Kalluri and Zeisberg, 2006 ; Yuan et al, 2017 ; Lee et al, 2019 ), immune killer cell subtype (IKCS, n = 62) ( Uzhachenko and Shanker, 2019 ), immune proantibody cell subtype (IPACS, n = 24) ( Oracki et al, 2010 ), and immune helper cell subtype (IHCS, n = 34) ( Banchereau and Steinman, 1998 ; Crotty, 2019 ; Figure 1A and Supplementary Table S2 ). The OS analysis indicated that IPCCS was associated with the poorest prognosis, and the other three subtypes were associated with similar or better prognosis than IPCCS ( P < 0.001, Figure 1B ).…”
Section: Resultsmentioning
confidence: 99%